Jesus and magic : freeing the gospel stories from modern misconceptions - Horsley, Richard A. (Eugene, Oregon : Cascade Books, 2014)
It has become standard in modern interpretation to say that Jesus performed miracles, and even mainline scholarly interpreters classify Jesus's healings and exorcisms as miracles. Some highly regarded scholars have argued, more provocatively, that the healings and exorcisms were magic, and that Jesus was a magician. As Richard Horsley points out, if we make a critical comparison between modern interpretation of Jesus's healing and exorcism, on the one hand, and the Gospel stories and other ancient texts, on the other hand, it becomes clear that the miracle and magic are modern concepts, products of Enlightenment thinking. Jesus and Magic asserts that Gospel stories do not have the concepts of miracle and magic. What scholars constructed as magic turns out to have been ritual practices such as songs (incantations), medicines (potions), and appeals to higher powers for protection. Horsley offers a critical reading of the healing and exorcism episodes in the Gospel stories. This reading reveals a dynamic relationship between Jesus the healer, the trust of those coming for healing, and their support networks in local communities. Horsley's reading of the Gospel stories gives little or no indication of divine intervention. Rather, the healing and exorcism stories portray healings and exorcisms.
Includes bibliographical references.
Description based on online resource; title from PDF title page (EBSCO, viewed February 16, 2015).
Keywords: Jesus Christ -- Miracles; Bible. -- Criticism, interpretation, etc; Magic, Ancient; Healing in the Bible; Miracles -- Biblical teaching; Exorcism -- Biblical teaching; RELIGION / Biblical Studies / Jesus, the Gospels & Acts; RELIGION / Biblical Studies / New Testament; Electronic books